2013
DOI: 10.1115/1.4007612
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Verification of a New Design for Cantilevered Stators With Large Hub Clearances

Abstract: Proportionally large relative radial clearances can be found within the rear stages of multistage axial compressors of gas turbines and aero engines, with significant impact on their efficiency. A new three-dimensional design for cantilevered stators in axial compressors is presented, with the aim of improving the overall efficiency and losses of rear stage vanes with large relative hub clearances. The new vane design comprises an unconventional dihedral, with special consideration to reduce the losses caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Wang, Chen, Wu, and Ren (2014) have shown good agreements of compressor performance maps between the computed results and the experimental data in a counter-rotating axial compressor when using the Spalart-Allmaras model. Lange, Vogeler, Mailach, and Gomez (2013) have shown that the NUMECA FINE-Turbo-computed blade pressure distributions have quite good agreement with the experiment. In addition, the separations predicted by the Spalart-Allmaras model are validated by using the k-model, indicating that the achieved results are not the function of the turbulence model.…”
Section: Cfd Validationssupporting
confidence: 54%
“…Wang, Chen, Wu, and Ren (2014) have shown good agreements of compressor performance maps between the computed results and the experimental data in a counter-rotating axial compressor when using the Spalart-Allmaras model. Lange, Vogeler, Mailach, and Gomez (2013) have shown that the NUMECA FINE-Turbo-computed blade pressure distributions have quite good agreement with the experiment. In addition, the separations predicted by the Spalart-Allmaras model are validated by using the k-model, indicating that the achieved results are not the function of the turbulence model.…”
Section: Cfd Validationssupporting
confidence: 54%
“…15 and 16 is scaled using Eq. (8). The non-dimensional coordinate x rel and y rel are normalized with the axial chord length, starting at the leading edge.…”
Section: Penny Cavity Flowmentioning
confidence: 99%
“…VSVs for both designs exist, as shown, for example, by Escuret [7]. The hub clearance of cantilevered stator vanes and the development of the hub clearance vortex have been investigated, for example, by Lange [8]. Shrouded VSVs are mounted on the hub on an inner ring.…”
Section: Introductionmentioning
confidence: 99%
“…The distributions of averaged circumferential static pressure coefficient, C p , at five spanwise points of the rotor and stator for the prototype and model A at design point are shown in Figures 5 and 6. C p is defined as C p = P P total,in (11) where P and P total,in denote the surface static pressure and the total pressure at inlet. The static pressure distributions of numerical results of prototype and model A are shown in Figure 5.…”
Section: Comparison Of the Prototype And Scaled-up Low-speed Model Amentioning
confidence: 99%
“…Lyes optimized the high-pressure compressor through research on blade bending and sweeping based on a low-speed model [7], which was also used for sweep and dihedral blading studies by RR Company and Cambridge University [8,9]. Besides, Boos and Lange also carried out a high loaded blading investigation on this large-scale, low-speed compressor [10,11]. Zhang to reached performance optimization of a low-speed axial rotor by three-dimensional (3D) optimization with numerical computation, and then the experiments were carried out for validation of the numerical results [12,13].…”
Section: Introductionmentioning
confidence: 99%